Bibliographic reference management: the role of technological appropriation in students - Castro Pérez, Luis Alvarado (2022)
Purpose: Over the past two decades, bibliographic reference management software has evolved as an exampleof technical innovation. Students believe reference management software, such as Mendeley, Zotero, Endnote, and Refworks, to be a modern tool and a tremendous help when conducting academic research. Consequently, this study aims to emphasize the significance of bibliographic reference management software. Design/methodology/approach: This research wasconducted using Bibliometricanalysis. For this aim, relevant papers were selected for review, and after screening, 18 papers were finalized. In different years of reviewed published research papers, authors apparently employed varying research procedures. Findings: The results suggested that reference management software improves the trustworthiness of student academic research. The perceptions of various pupils vary based on the reference management software they use. Software for managing references promotes writing and critical thinking in academic research. Practical implications The research has significant practical significance as a valuable supplement to the trend of student adoption of reference management software for academic research. The software developers can also get information from this study by evaluating the significance of bibliographic management software, the extent of its quick emergence, and the increasing tendency of students to adopt it for their theses and other research projects. Originality/value: The unique contribution of this study to the corpus of knowledge gives it theoretical relevance. As it is an important addition to the literature regarding the selection of student reference management software in academic institutions, it is included here.